The Challenges and Best Practices of English Language Teaching in Indonesian Secondary School: A Systematic Literature Review - AZAHRA, Mona; ABDULRAHMAN, Tryanti; TAMELA, Ellis (Politeknik Negeri Ujung Pandang, 2025)
This systematic literature review of seventy-one studies provides a comprehensive overview of English language teaching in Indonesian senior and vocational high schools over the last 10 years. Using the Publish or Perish (PoP) tool, a systematic search was conducted through Google Scholar and CrossRef. The study identified three main themes: current trends, challenges encountered by teachers and students, and best practices. Most of the studies were qualitative and published in SINTA-indexed journals. The result highlighted several challenges, including barriers to teaching and learning, Inadequate infrastructure, concerns about student well-being, and low student motivation and engagement. Meanwhile, best practices include continuous teacher development, student-centered approaches, technology integration, language skill development, and support from schools and families. Tailoring sustainable implementation to the local context has the potential to improve teaching quality. The study highlights the need for coordinated collaboration among policymakers, educators, and stakeholders to ensure the effective implementation of the proposed recommendations.